2017
DOI: 10.13075/ijomeh.1896.01140
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of gloves and protective clothing materials to permeation of cytostatic solutions

Abstract: Objectives: The objective of the work was to determine the resistance of selected protective clothing and glove materials to permeation of cytostatics such as docetaxel, fluorouracil, and doxorubicin. Material and Methods: The following glove materials were used: natural rubber latex (code A), acrylonitrile-butadiene rubber (code B) and chloroprene rubber (code C). In addition, we tested a layered material composed of a non-woven polyester (PES), a polypropylene (PP) film, and a non-woven PP used for protectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…Moreover, some authors corroborate our findings showing modifications in surface morphology after contact with various solvents 5,14,15,[17][18][19] . Ethanol, acetone, methacrylate, or other substances, such as eugenol, bleaching agents, phosphoric acid, or some drugs, are frequently used in the daily dental routine and have also been associated with changes in the gloves' morphology 9,13 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, some authors corroborate our findings showing modifications in surface morphology after contact with various solvents 5,14,15,[17][18][19] . Ethanol, acetone, methacrylate, or other substances, such as eugenol, bleaching agents, phosphoric acid, or some drugs, are frequently used in the daily dental routine and have also been associated with changes in the gloves' morphology 9,13 .…”
Section: Discussionsupporting
confidence: 90%
“…The risk of gloves micro-perforations is imminent, facilitating microorganisms' course before and during clinical care [5][6][7][8][10][11][12] . Even though surgical sterile or non-sterile gloves provide a physical barrier in clinical procedures 6,8,[10][11][12] , it is mandatory to conduct comprehensive tests to ensure the quality of these materials as an effective barrier against pathogens [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] . Among those methods, electronic devices 20,21 , pressurized air influx, looking for blood in the surgeon's hand 6 , water filling, and bacterial assays have been applied 8,11,12,22 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has already been suggested that excipients may facilitate the passage of anticancer drugs through gloves. 24 In our study it is impossible to exclude excipients from playing a role in the rate of permeation of carmustine (ethanol and water) and busulfan (dimethylacetamide and macrogol 400). However, the role of the excipient can be ruled out in the case of thiotepa as it consists of water.…”
Section: Discussionmentioning
confidence: 87%
“…Moreover, the number of chemicals tested varied considerably from one study to the next, ranging from a single chemical to 15 chemicals, but many studies used fewer than 7 chemicals. 9,10,[21][22][23][24][25][26]29 This makes it harder to compare the relative behaviour of different chemicals under identical experimental conditions with the same gloves. In this study we tested 27 chemicals, and only 3 had permeation rates above the US standard ASTM D-6978-05 (carmustine, busulfan and thiotepa) with some gloves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation